Positive electrode and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- KR1020240003332
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-01-20
- Filing Date
- 2024-01-09
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2044-01-09
Smart Images

Figure 112024002892584-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a positive electrode and a non-aqueous electrolyte secondary battery (hereinafter also referred to as a battery) equipped with the same. Background Technology
[0002] Japanese Patent Publication No. 2018-139213, Japanese Patent Publication No. 2022-114665, and Japanese Patent Publication No. 2022-100812 propose using carbon nanotubes (hereinafter also referred to as CNT) as a conductive material in the positive electrode of a battery.
[0003] When CNTs are used as a conductive material in the positive electrode composite layer of a battery, it is possible to improve output characteristics or high-rate characteristics due to their high conductivity. In addition, by reducing the content of CNTs in the positive electrode composite layer and increasing the content of the positive electrode active material, it is possible to increase energy density (increase capacity). On the other hand, when CNTs are used in the positive electrode composite layer, the problem is that electrode melting properties (hereinafter also referred to as melting properties) decrease along with the decrease in the resistance of the composite layer.
[0004] The objective of the present invention is to provide a positive electrode capable of exhibiting high initial capacity and high meltability, along with excellent charge-discharge efficiency, and a battery including the same.
[0005] The present invention provides the following positive electrode and battery.
[0006] [1] It is a positive electrode containing a positive electrode composite layer, and
[0007] The above positive electrode composite layer comprises active material particles and CNTs, and
[0008] The content of the above CNT is 0.05 wt% or more and 0.45 wt% or less based on the total solid content of 100 wt% of the above positive electrode composite layer, and
[0009] The positive electrode, wherein the area resistivity of the composite layer of the above positive electrode composite layer is 0.10Ω·cm² or more and 0.70Ω·cm² or less.
[0010] [2] The positive electrode described in [1], having a CNT content of 0.15 wt% or more.
[0011] [3] The positive electrode described in [1] or [2], the area resistivity of the composite layer is less than 0.45 Ω·cm².
[0012] [4] The positive electrode described in any one of [1] to [3] has a fill density of 3.5 g / cm³ or more of the positive electrode layer.
[0013] [5] A positive electrode described in any one of [1] to [4], wherein the ratio of the active material particles to Ni is 60% or less.
[0014] [6] The above active material particles include large particles and small particles, as described in any one of [1] to [5].
[0015] [7] The positive electrode described in [6], the average particle size of the above large particles is 12 to 20 μm.
[0016] [8] The positive electrode described in [6] or [7], the average particle size of the above small particles is 2 to 6 μm.
[0017] [9] The ratio of the average particle size of the small particles to the average particle size of the large particles is 1 / 10 to 1 / 2, as described in any of [6] to [8].
[0018]
[10] The above CNT is a positive electrode described in any one of [1] to [9], comprising a surface-modified CNT.
[0019]
[11] The positive electrode composite layer described above is a positive electrode described in any one of [1] to
[10] , which further includes additives.
[0020]
[12] A battery comprising a positive electrode as described in any of [1] to
[11] .
[0021] The above and other objects, features, aspects, and advantages of the present invention will become clear from the following detailed description of the invention as understood in conjunction with the accompanying drawings. Brief explanation of the drawing
[0022] FIG. 1 is a schematic diagram illustrating an example of the configuration of a positive pole in the present embodiment. Figure 2 is a schematic flowchart illustrating a method for manufacturing a positive electrode. FIG. 3 is a schematic diagram illustrating an example of the configuration of a battery in the present embodiment. FIG. 4 is a schematic diagram illustrating an example of the configuration of an electrode body in the present embodiment. Specific details for implementing the invention
[0023] Embodiments of the present invention will be described below with reference to the drawings, but the present invention is not limited to the following embodiments. In all of the following drawings, the scale is appropriately adjusted to facilitate understanding of each component, and the scale of each component shown in the drawings does not necessarily correspond to the actual scale of the component.
[0024] Drama
[0025] The positive electrode includes a positive electrode composite layer. The positive electrode composite layer includes active material particles and CNTs. The content of CNTs in the positive electrode composite layer is 0.45 wt% or less based on 100 wt% of the total solid content of the positive electrode composite layer. Since the content of CNTs in the positive electrode composite layer is within the above range, there is a tendency for high initial capacity and high meltability to be easily exhibited, along with excellent charge-discharge efficiency. From the perspective of charge-discharge efficiency, initial capacity, and meltability, the content of CNTs in the positive electrode composite layer is preferably 0.40 wt% or less based on 100 wt% of the total solid content of the positive electrode composite layer. In addition, from the perspective of charge-discharge efficiency, the content of CNTs in the positive electrode composite layer is preferably 0.15 wt% or more based on 100 wt% of the total solid content of the positive electrode composite layer. Details of the CNTs will be described later.
[0026] The area resistivity of the positive electrode composite layer is 0.10 Ω·cm² or higher. Since the area resistivity of the positive electrode composite layer is within the above range, excellent charge-discharge efficiency is achieved, and there is a tendency for high initial capacity and high meltability to be easily exhibited. From the perspective of meltability, the area resistivity of the positive electrode composite layer is preferably 0.11 Ω·cm² or higher, and more preferably 0.12 Ω·cm² or higher. From the perspective of charge-discharge efficiency, the area resistivity of the positive electrode composite layer is preferably less than 0.45 Ω·cm², and more preferably 0.40 Ω·cm² or lower. The area resistivity of the positive electrode composite layer can be controlled, for example, by adjusting the type and content of CNTs or by adjusting the mixing process conditions of the composite layer slurry. The area resistivity of the positive electrode composite layer is measured according to the method described in the section of the examples below.
[0027] The active material particles may be particles containing a lithium transition metal composite oxide. The crystal structure of the lithium transition metal composite oxide is not particularly limited and may be a layered structure, a spinel structure, an olivine structure, etc. As for the lithium transition metal composite oxide, a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element is preferred. Specifically, examples include a lithium nickel-based composite oxide, a lithium cobalt-based composite oxide, a lithium manganese-based composite oxide, a lithium nickel manganese-based composite oxide, a lithium nickel cobalt manganese-based composite oxide, a lithium nickel cobalt aluminum-based composite oxide, and a lithium iron nickel manganese-based composite oxide. When the active material particles contain nickel, the nickel content ratio relative to the metal elements excluding lithium in the active material particles may be, for example, 60 mol% or less. The active material particles may be surface-coated.
[0028] The active material particles may include, for example, layered metal oxides. The layered metal oxide is, Formula (1):
[0029]
[0030] It is represented by. In Equation (1), “a1” satisfies the relationship “-0.3 ≤ a1 ≤ 0.3”. “x1” satisfies the relationship 0.1 ≤ x1 ≤ 0.6. “Me 1 " represents at least one type selected from the group consisting of Co, Mn, Al, Zr, Ti, V, Cr, Fe, Cu, Zn, B, Mo, Sn, Ge, Nb, and W.
[0031] The active material particles may each contain multiple large particles and multiple small particles. The large particles have a larger average particle size compared to the small particles. The average particle size of the large particles may be, for example, 12 μm or more and 20 μm or less, and preferably 14 μm or more and 18 μm or less. The average particle size of the small particles may be, for example, 2 μm or more and 6 μm or less, and preferably 3 μm or more and 6 μm or less. In this specification, the average particle size refers to the particle size (hereinafter also referred to as D50) at which the cumulative particle volume from the small particle size side in the volume-based particle size distribution is 50% of the total particle volume. The average particle size can be measured by laser diffraction and scattering methods. The ratio of the average particle size of the small particles to the average particle size of the large particles may be, for example, 1 / 10 to 1 / 2.
[0032] The content of active material particles in the positive electrode composite layer may be, for example, 70 wt% or more based on the total solid content of 100 wt% of the positive electrode composite layer, preferably 80 to 99 wt%, and more preferably 90 to 99 wt% or less.
[0033] CNTs are fibrous carbons having a structure in which graphene forming a carbon hexagonal network is rounded into a tubular shape. CNTs possess properties such as a high aspect ratio and excellent electronic conductivity. Examples of CNTs include single-layer CNTs formed by a single layer of graphene or multilayer CNTs formed by two or more layers of graphene. Multilayer CNTs are preferred from the perspective of thermal and chemical stability. Preferably, CNTs include CNTs whose surface has been modified by acid treatment or heat treatment.
[0034] CNTs may be purchased from the market or manufactured using conventionally known methods for producing CNTs. Examples of such methods include chemical vapor deposition (CVD), arc discharge, and laser evaporation.
[0035] The positive electrode composite layer may include a conductive material other than CNT. As a conductive material other than CNT, carbon black such as acetylene black (AB) or other carbon materials (e.g., graphite) may be suitably used.
[0036] The positive electrode composite layer may include a binder. Examples of binders include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide (PI), polyamide (PA), polyamideimide (PAI), butadiene rubber (BR), styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), styrene-ethylene-butylene-styrene block copolymer (SEBS), carboxymethylcellulose (CMC), or combinations thereof. The content of the binder in the positive electrode composite layer may be, for example, 0.5 to 10 wt% based on 100 wt% of the total solid content of the positive electrode composite layer, and preferably 1.0 to 5 wt%. The positive electrode composite layer may include known additives that can be used for the positive electrode.
[0037] The positive electrode (100) illustrated in FIG. 1 has a positive electrode composite layer (20) formed on a positive electrode substrate (10). The positive electrode composite layer (20) may be formed directly or indirectly on one or both sides of the positive electrode substrate (10). The positive electrode substrate (10) may be a conductive sheet made of, for example, an Al alloy foil, a pure Al foil, etc. The positive electrode composite layer (20) includes active material particles (21) and CNTs (22). The positive electrode composite layer (20) may further include a binder, an additive, etc. The active material particles (21) include large particles (23) and small particles (24).
[0038] The positive electrode composite layer (20) may have a thickness of, for example, 10 μm or more and 200 μm or less. The positive electrode composite layer (20) may have high density. The density of the positive electrode composite layer (20) may, for example, be 3.5 g / cm³ or more, 3.7 g / cm³ or more, 3.8 g / cm³ or more, or 3.9 g / cm³ or more. The density of the positive electrode composite layer (20) may, for example, be 4.0 g / cm³ or less.
[0039] The method for manufacturing the positive electrode (100) in this embodiment includes preparing (A1), coating (B1), drying (C1), and compressing (D1) the positive electrode slurry as shown in FIG. 2.
[0040] In the preparation (A1) of a positive electrode slurry, a positive electrode slurry comprising active material particles and CNTs is prepared. The positive electrode slurry is prepared by dispersing the active material particles in a dispersion medium. The organic solvent may include, for example, at least one selected from the group consisting of N-methyl-2-pyrrolidone (NMP), tetrahydrofuran (THF), dimethylformamide (DMF), methyl ethyl ketone (MEK), and dimethyl sulfoxide (DMSO). The amount of organic solvent used is optional. The positive electrode slurry may have any solid content concentration (mass fraction of solids). The slurry may have, for example, a solid content concentration of 40% to 80%. Any stirring device, mixing device, or dispersion device may be used for mixing.
[0041] The coating (B1) may include forming a coating film by coating a positive electrode slurry onto the surface of a substrate. In the present embodiment, the positive electrode slurry may be coated onto the surface of the substrate by any coating device. For example, a slot die coater, a roll coater, etc. may be used. The coating device may be capable of multi-layer coating.
[0042] Drying (C1) may include drying the coating film by heating it. In the present embodiment, any drying device may be used as long as the coating film can be heated. For example, the coating film may be heated by a hot air dryer, etc. As the coating film is heated, the organic solvent may evaporate. By doing so, the organic solvent may be substantially removed.
[0043] In the present embodiment, compression (D1) may include compressing the coating film after drying to form a positive electrode composite layer (20), any compression device may be used. For example, a rolling mill may be used. The coating film after drying is compressed, the positive electrode composite layer (20) is formed, and the positive electrode (100) is completed. The positive electrode (100) may be cut to a predetermined flat size according to the specifications of the battery. The positive electrode (100) may be cut to have a strip-like flat shape, for example. The positive electrode (100) may be cut to have a rectangular flat shape, for example.
[0044] Battery
[0045] The battery may be a lithium-ion battery. FIG. 3 is a schematic diagram illustrating an example of a lithium-ion battery in the present embodiment. The battery (200) shown in FIG. 3 may be a lithium-ion battery, for example, a main power source for an electric vehicle or a power source for power assist. The battery (200) includes an outer body (90). The outer body (90) houses an electrode body (50) and a non-aqueous electrolyte (not shown). The electrode body (50) is connected to a positive electrode terminal (91) by a positive electrode current collector (81). The electrode body (50) is connected to a negative electrode terminal (92) by a negative electrode current collector (82). FIG. 4 is a schematic diagram illustrating an example of an electrode body in the present embodiment. The electrode body (50) is of the wound type. The electrode body (50) includes a positive electrode (100), a separator (70), and a negative electrode (60). That is, the battery (200) includes a positive electrode (100). The positive electrode (100) includes a positive electrode composite layer (20) and a positive electrode substrate (10). The negative electrode (60) includes a negative electrode active material layer (62) and a negative electrode substrate (61).
[0046] The non-aqueous electrolyte comprises a solvent and a lithium salt. The solvent is aprotic. The solvent may contain any component. The solvent may include, for example, at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), diethyl carbonate (DEC), 1,2-dimethoxyethane (DME), methyl formate (MF), methyl acetate (MA), methylpropionate (MP), and γ-butyrolactone (GBL).
[0047] The lithium salt is a supporting electrolyte. The lithium salt is dissolved in a solvent. The lithium salt may include at least one selected from the group consisting of, for example, LiPF6, LiBF4, and LiN(FSO2)2. The lithium salt may have a molar concentration of, for example, 0.5 mol / L or more and 2.0 mol / L or less, or a molar concentration of 0.8 mol / L or more and 1.2 mol / L or less.
[0048] In addition to the solvent and lithium salt, the non-aqueous electrolyte may further contain any additive. For example, the electrolyte may contain an additive in a mass fraction of 0.01% or more and 5% or less. The additive may include at least one selected from the group consisting of, for example, vinylene carbonate (VC) and vinylethylene carbonate (VEC).
[0049] [Example]
[0050] The present invention will be explained in more detail below through examples. Unless otherwise noted, “%” and “parts” in the examples are mass % and mass parts.
[0051] <Example 1>
[0052] Active material particle 1 (lithium nickel composite oxide with a particle size of 14 to 18 μm) and active material particle 2 (lithium nickel composite oxide with a particle size of 3 to 6 μm) were mixed in a 1:1 ratio, and the mixture was mixed such that the said mixture was 98.55 parts by mass, CNT as a conductive material was 0.45 parts by mass, and PVdF as a binder was 1.0 part by mass, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode composite slurry. A positive electrode composite layer was formed by applying the said slurry to a current collector made of aluminum foil. Afterward, it was dried, rolled to a predetermined thickness using a rolling roller, cut to a predetermined size, and an aluminum tab was installed to form a positive electrode.
[0053] <Examples 2 to 5, Comparative Examples 1 to 3>
[0054] A positive electrode was manufactured in the same manner as in Example 1, except for the conductive material mixing ratio among the conductive material and composite layer shown in Table 1.
[0055] [Production of the Play]
[0056] A graphite negative electrode active material, carboxymethylcellulose (CMC) as a thickener, and styrene-butadiene rubber (SBR) as a binder were each weighed in a mass ratio of 98:1:1, and dispersed in water to prepare a negative electrode composite slurry. A negative electrode composite layer was formed by applying this negative electrode composite slurry to a current collector made of copper foil. Afterward, it was dried, rolled to a predetermined thickness using a rolling roller, cut to a predetermined size, fitted with a nickel tab, and used as a negative electrode.
[0057] [Preparation of Non-Aqueous Electrolytes]
[0058] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:30:40. Lithium hexafluorophosphate (LiPF6) was added to the mixed solvent at a concentration of 1.15 mol / liter. Additionally, vinylene carbonate (VC) was added at an addition rate of 1.0 mass% relative to the total mass of the mixed solvent to prepare a non-aqueous electrolyte.
[0059] [Evaluation of Area Resistivity of the Positive Pole Composite Layer]
[0060] With the volume resistivity of the aluminum foil current collector set to 2.70E-06[Ω], the area resistivity (Ω·cm²) of the positive electrode composite layer of the positive electrode plate was measured using an electrode resistance measurement system (HIOKI RM2610). The results are shown in Table 1.
[0061] [Evaluation of Initial Capacity and Charge / Discharge Efficiency]
[0062] (Production of test cells)
[0063] The positive and negative electrodes fabricated above were laminated with a polyolefin separator interposed to fabricate a laminated electrode body. This electrode body was housed within an outer casing made of an aluminum laminate sheet, and after injecting the non-aqueous electrolyte prepared above, the opening of the outer casing was sealed to obtain a test cell.
[0064] (Evaluation of initial capacity and charge / discharge efficiency)
[0065] For the test cell fabricated above, constant current charging was performed at a current density of 0.2 mA / cm² under a temperature condition of 25°C until the voltage reached 4.25 V, and constant voltage charging was performed at 4.25 V until the current density reached 0.04 mA / cm² to determine the charging capacity (initial capacity). After a 10-minute rest period, constant current discharge was performed at a current density of 0.2 mA / cm² until the voltage reached 3.0 V to determine the discharge capacity. The charge / discharge efficiency was calculated using the above discharge capacity and charging capacity according to the following formula.
[0066] Charge / Discharge Efficiency = [Discharge Capacity] / [Charge Capacity] × 100
[0067] The ratio was calculated when the initial capacity and charge / discharge efficiency of Comparative Example 1 were set to 100. The results are shown in Table 1.
[0068] [Assessment of Decisiveness]
[0069] A test cell for evaluating electrode meltability was connected in parallel with a constant voltage power source with a maximum current of 200A, and a nail penetration test was performed to allow a current simulating a large cell to flow. The heating rate (W) after electrode melting (after removing the nail) was measured, and the ratio of the heating rate to the heating rate of Comparative Example 1, set to 100, was calculated as meltability. The results are shown in Table 1.
[0070]
[0071] In Table 1, cases where the initial capacity was 100 or more, the charge / discharge efficiency was 99.5 or more, and the electrode meltability was 80 or more were judged as ○, and cases other than that were judged as ×. In Examples 1 to 5 according to the present invention, excellent charge / discharge efficiency, high initial capacity, and high meltability could all be achieved.
[0072] Although embodiments of the present invention have been described, the embodiments disclosed herein should be considered illustrative in all respects and not restrictive. The scope of the present invention is defined by the claims, and all modifications within the meaning and scope equivalent to the claims are intended to be included.
Claims
Claim 1 A positive electrode comprising a positive electrode composite layer, wherein the positive electrode composite layer comprises active material particles and carbon nanotubes, the content of the carbon nanotubes is 0.05 wt% or more and 0.45 wt% or less based on 100 wt% of the total solid content of the positive electrode composite layer, and the area resistivity of the composite layer of the positive electrode composite layer is greater than 0.16 Ω·cm² and less than 0.45 Ω·cm². Claim 2 A positive electrode according to claim 1, wherein the carbon nanotube content is 0.15 wt% or more. Claim 3 delete Claim 4 In claim 1, the positive electrode has a composite filling density of the positive electrode composite layer of 3.5 g / cm³ or more. Claim 5 A positive electrode according to claim 1, wherein the nickel content ratio to the metal element excluding lithium among the active material particles is 60 mol% or less. Claim 6 In claim 1, the positive electrode comprises active material particles including large particles and small particles. Claim 7 In claim 6, the positive electrode, wherein the average particle size of the above-mentioned large particles is 12 to 20 μm. Claim 8 In claim 6, the positive electrode, wherein the average particle size of the small particles is 2 to 6 μm. Claim 9 In claim 6, the ratio of the average particle size of the small particles to the average particle size of the large particles is 1 / 10 to 1 / 2, a positive electrode. Claim 10 In claim 1, the carbon nanotube comprises a surface-modified carbon nanotube, forming a positive electrode. Claim 11 In claim 1, the positive electrode composite layer further comprises an additive, a positive electrode. Claim 12 A non-aqueous electrolyte secondary battery comprising the positive electrode described in claim 1.
Citation Information
Patent Citations
Positive electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2017084521A
Positive electrode for secondary battery and secondary battery comprising the same
JP2021007109A
Positive electrode for lithium secondary battery and lithium secondary battery including the same
JP2022137007A
Nonaqueous electrolyte secondary battery
JP2022138392A
Positive electrode for secondary battery and secondary battery including the same
JP7062157B2
